'Some women are proud of their experience and I have to respect that': an interview-study about midwives' experiences in caring for infibulated women during childbirth in Sweden - Louise Lundborg; Anna Wahlberg; Nana Gilmore; Cecilia Boisen (CSIRO Publishing, 2021)
ABSTRACT INTRODUCTIONAs the immigrant communities in high-income countries become larger and increasingly multicultural and ethnically diverse, health professionals are more likely to see girls and women with, or at risk of, female genital mutilation or 'cutting' (FGM/C) in clinical practice. To provide good care and support, other health-care professionals may learn from the experiences of midwifes caring for infibulated women during labour in Sweden. AIMTo describe Swedish midwives' experiences in caring for infibulated women during labour. METHODSThis is a qualitative study. Semi-structured interviews with six midwives working at obstetric clinics in Sweden used open-ended questions. The interviews were recorded, transcribed verbatim and analysed by using thematic analysis. RESULTSTwo main themes were identified: experienced challenges during the process of labour; and midwives' emotional experiences. Midwives experienced challenges during their professional encounters with infibulated women and a variety of emotions were evoked when caring for these women during labour. Lack of general guidelines and standardised routines complicated their work. DISCUSSIONThe midwives' experiences were negatively affected by organisational factors and being emotionally affected by the fact that these women were not perceived to be given appropriate care because of their FGM/C. Policymakers in Sweden should consider implementing national guidelines for how to care for women exposed to FGM/C, ideally at an early stage in their reproductive life.